An acetyltransferase family required for biosynthesis of diverse marine carotenoids - Tianjun Cao; Xuechun Bai; Tingting You; Yanyou Jiang; Martin Lohr; Xiaobo Li (Proceedings of the National Academy of Sciences, 2026)
Chromalveolate algae such as diatoms, haptophytes, and dinoflagellates are main contributors to oceanic primary production, sustaining marine ecosystems and global carbon cycles while synthesizing a striking array of acetylated carotenoids like fucoxanthin and peridinin. These pigments optimize photosynthetic light harvesting in the algae and offer nutritional benefits for humans, yet knowledge of their biosynthetic pathways is still incomplete, particularly the shared acetylation step. By screening 39 candidate genes in the diatom Phaeodactylum tricornutum , we identified an enzyme with x anthophyll ac etyl t ransferase (XACT) activity that is indispensable for this modification. Disrupting XACT in Phaeodactylum and the eustigmatophyte Nannochloropsis oceanica abolished xanthophyll acetylation. Phylogenetic analyses revealed that XACT is exclusively present in chromalveolates synthesizing acetylated xanthophylls. In vitro assays with recombinant XACT enzymes from Phaeodactylum , Nannochloropsis , the brown alga Ectocarpus siliculosus , the dinoflagellate Symbiodinium tridacnidorum , and a haptophyte confirmed their general activity toward allenic precursor carotenoids but exhibited lineage-specific substrate preferences, explaining the diversified carotenoid structures across lineages. The broad substrate specificity of XACT from Phaeodactylum led us to reinvestigate the substrate specificities of other enzymes involved in fucoxanthin formation, indicating that fucoxanthin biosynthesis in diatoms proceeds via a multibranched rather than a linear pathway. XACT from Ectocarpus showed a distinctly narrow substrate spectrum, providing key evidence for the order of the two previously proposed steps in brown algal fucoxanthin biosynthesis. Our work resolves a long-standing gap in marine carotenoid biosynthesis and identifies the relaxed substrate specificities of the enzymes involved as an important driver for the multitude of algal carotenoid structures.